Sodium in Io's extended atmosphere. - Schneider, Nicholas McCord. (The University of Arizona., 1988)
This dissertation combines several new observations of the Io sodium cloud to create a consistent picture of the extended Io atmosphere and its interaction with the Jovian plasma torus. I used the LPL echelle spectrograph to obtain three types of high-resolution spectra of the extended sodium cloud at the sodium D-lines (5890, 5896Å). The first class of observations made use of the mutual satellite eclipses of 1985 to probe the density profile of the atmosphere in the range 1.4 to 10 Io radii, a previously unstudied region. The second type of observation examined the sodium emission in Io's immediate vicinity, allowing an accurate measurement of the velocity structure around Io. The final method employed a high-sensitivity detector to study faint jets of high-speed sodium farther out in the extended cloud. The synthesis of these three data sets results in a better understanding of how sodium is distributed about Io as a function of position and velocity. Io's extended atmosphere is composed of many kinematically distinct components. The distribution in space is linked to their characteristic velocities, with low-energy sodium confined near Io and faster atoms (10 to 100 km sec⁻¹) prevalent beyond ∼25 Io radii. The sodium density profile is steep near Io and shallower outside 5.6 Io radii, the effective limit of Io's gravity. The data indicate that the atmosphere is collisionally thick near the surface, but becomes thin by an altitude of ∼700 km. The upper limit of the exobase location is derived from reliable sodium density measurements made during the satellite eclipses. The lower limit is indirectly inferred from the velocity distribution of sodium near Io and the nature of high-speed jets far from Io. The high-speed sodium jets reveal a new type of close interaction between the corotating plasma and Io's atmosphere. The morphology and brightness of the jets require a two-reaction process, in which atmospheric sodium is ionized, accelerated to high speeds, and then charge-exchanges with other sodium atoms. These processes must occur near the atmospheric exobase, indicating that Io's atmosphere is not completely protected from the plasma flow.